CONODONT BIOSTRATIGRAPHY OF THE LATE TRIASSIC SEQUENCE OF MONTE COCUZZO (CATENA COSTIERA, CALABRIA, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1997)
Preliminary results are reported from an investigation of the conodont associations found in the Late Triassic carbonate succession of the so-called "Catena Costiera Calabrese" that crops out in the tectonic window of Monte Cocuzzo. The succession of Colle del Crapio consists of alternating carbonate mud, breccia and calciturbidites deposited in a toe-of-slope to basin setting and contains rich and well-preserved conodont faunas pertaining to two biozones. The lower zone is characterised by the occurrence of Epigondolella slovakensis and may be referred to the Late Norian (Sevatian). The upper zone is characterised by Misikella hernsteini associated with M. posthernsteini. The chronostratigraphic setting of the latter zone is more controversial, as it may be regarded as latest Sevatian (Upper Norian) according to Krystyn (1990) and Golebiowski (1990), while according to the zonation of Kozur & Mock (1991) the first occurrence of M. posthernsteini marks the beginning of the Rhaetian stage.